Demokrasi Indonesia: Antara Barat dan Islam: Karakteristik Demokrasi Indonesia: Kajian Perbandingan antara Nilai-Nilai Barat dan Islam - Fachri Khoerudin (Journal of Islamic and Occidental Studies, 2023)
This article began with the question of whether Indonesian democracy is based on religious values (Islam) or whether it purely adopts Western values. This was because debates regarding this question continue to be echoed in the history of the Indonesian nation’s journey. As a result, there were groups that accepted and fought secular Western democracy to be implemented in Indonesia, there were also those who rejected it blindly, and there were those who thought democracy was not all against Islam, but it did not fully represent Islamic politics absolutely. This article examines the technical and philosophical characteristics of Indonesian democracies. This article is qualitative used library research for data collection from books, journal articles, and documents related to the Indonesian democracy. The collected data were then processed using descriptive analysis methods. This study found that Indonesia adopts a unique democratic system in which Islamic values are embedded and in harmony with it.